Antara Idealitas dan Realitas: Seberapa dalam Internalisasi Apostolicam Actuositatem Membentuk Motivasi Kerasulan Pemuda Katolik - Gabriel Aldo Nagama; Yustinus J.W. Yuniarto; Anselmus Joko Prayitno; Dr. Andarweni Astuti (Jurnal Filsafat dan Teologi Katolik, 2026)
The document Apostolicam Actuositatem is a magisterial teaching issued by the Roman Catholic Church that addresses the apostolate of the laity. The present study responds to the contemporary issue of youth skepticism and apathy toward politics, government, and social engagement. The research subjects consisted of 34 members of Pemuda Katolik Komisariat Cabang Kota Semarang as respondents and six organizational board members as key informants. This study employed a mixed-method explanatory approach. Quantitative data were collected through questionnaires using a quota sampling technique, while qualitative data were obtained through in-depth interviews with six informants. The quantitative findings indicate that the internalization of Apostolicam Actuositatem influences apostolic motivation by 48%. The level of apostolic motivation among members in promoting the Pemuda Katolik Komisariat Cabang Semarang organization reached 68.2%. Furthermore, the internalization of Apostolicam Actuositatem toward the implementation of lay apostolate principles was measured at 48.4%. Qualitative findings from informants (N1–N6) reveal that members’ motivation in understanding Apostolicam Actuositatem is primarily driven by an inner calling, even among those who were previously unfamiliar with the document; this aligns with Article 1 of Apostolicam Actuositatem. Members’ efforts to promote the Pemuda Katolik Organization, both through internal organizational activities and initiatives outside the Church, correspond to Article 30. Moreover, the application of the principles of Apostolicam Actuositatem is implemented at every level of cadre formation within the Pemuda Katolik Organization of Komisariat Cabang Kota Semarang namely Mapenta, KKD, KKM, and KKL—in accordance with Article 22.